Beyond Price and Prosmotions: Uncovering the Drivers of Guest Choice at V Hotel and Residence Bandung - Fenny, Fenny; Suryati, Lili (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this study to determine how the price, product, promotion, purchasing decisions, and how much influence the price, the product, and promotions on consumer purchasing decisions This research is a census, the number of objects in a population of 100. The research method used in this research is descriptive analysis method. The data analysis technique used is the technique of correlation analysis and path analysis techniques. Correlation analysis techniques to determine the relationship between variables, while the technique of path analysis to determine how much influence the independent variables on the dependent variable. The software used to process and analyze the data of this study was SPSS version 23. The results showed that the variable conditions of the price, product,promotion and purchasing decisions included in both categories.